High-quality epitaxial, homogeneous anatase thin films by on-site controlled hydrolysis on LaAlO3 substrates and characterization - Sudu Hakuruge Dilan Priyankara Wijekoon; Kosuke Ono; Masaru Shimomura; Takahiko Kawaguchi; Naonori Sakamoto; Naoki Wakiya (Science and Technology of Advanced Materials)
The anatase form of TiO₂ is a widely studied material due to its broad range of applications. Epitaxial anatase thin films have attracted significant attention because of their enhanced electrical and optical properties. However, fabricating anatase thin films remains challenging due to their metastability and the need for highly sophisticated fabrication techniques. On-site controlled hydrolysis is a simple, cost-effective, and rapid method for producing smooth, compact thin films on various surfaces. In this study, we demonstrate a straightforward approach to fabricating highly oriented epitaxial anatase thin films on LaAlO₃ substrates using different solvent mixtures. The epitaxial orientation and film quality were analyzed using X-ray diffraction pole figures and rocking curves, while surface morphology was characterized by Scanning electron microscopy and atomic force microscopy. Our results indicate that thin film quality and morphology are primarily influenced by the annealing temperature rather than the choice of solvent or titanium precursor, confirming the feasibility of a scalable, low-cost epitaxial fabrication technique for anatase thin films.